Correction: Synthesis and antibiotic activity of oxazolidinone–catechol conjugates against Pseudomonas aeruginosa. Issue 46 (10th November 2015) - Paulen, Aurélie; Gasser, Véronique; Hoegy, Françoise; Perraud, Quentin; Pesset, Bénédicte; Schalk, Isabelle J.; Mislin, Gaëtan L. A.
Abstract : Correction for 'Synthesis and antibiotic activity of oxazolidinone–catechol conjugates against Pseudomonas aeruginosa ' by Aurélie Paulen, et al., Org. Biomol. Chem., 2016, DOI: 10.1039/c5ob01859e.